EFEKTIFITAS MEDIA ABAKUS UNTUK MENINGKATKAN KEMAMPUAN PENGURANGAN BAGI TUNARUNGU - Rita - Wahyuni (Universitas Negeri Padang, 2012)
This study against the background of the problems that appear in children with hearing impairment X class II diSLB Ampek Angkek Agam, who have difficulty in calculating the reduction of two-digit numbers. This is evident from the beginning of the ability of children in working out the problems we are given the 10 questions. Methodology of the study is a single subject research (SSR) with the ABA research design, namely a reduction in the ability to compare X Deaf children at Baseline I condition (A1), the condition Intervention (B), and Baseline II (A2). Data analysis techniques are used based on the observed data in the form of Visual Analysis Of Graph. The results of this study aimed at analyzing data from a given reduction of 10 questions, the analysis of the conditions and data analysis among the conditions that indicate a change in the ability of a reduction in number as many as 10 questions on the child's X into a better direction. Obtained overlape percentage is 0% and 42%.